If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(t + -13) + 8 = 20 Reorder the terms: 4(-13 + t) + 8 = 20 (-13 * 4 + t * 4) + 8 = 20 (-52 + 4t) + 8 = 20 Reorder the terms: -52 + 8 + 4t = 20 Combine like terms: -52 + 8 = -44 -44 + 4t = 20 Solving -44 + 4t = 20 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '44' to each side of the equation. -44 + 44 + 4t = 20 + 44 Combine like terms: -44 + 44 = 0 0 + 4t = 20 + 44 4t = 20 + 44 Combine like terms: 20 + 44 = 64 4t = 64 Divide each side by '4'. t = 16 Simplifying t = 16
| (-4v^2+8v+4)+(3v^2-5v-7)-(-v^2+5v+4)=0 | | 2(q+2)=10 | | (12x-9)+(2x+21)=360 | | 2 ( q + 2 ) = 10 | | (-.517m)(-.6n)= | | 2(s-11)+7=15 | | 5+13p-3=9p+46-7p | | 12x-5x=27 | | 13-p=16 | | 12x-5x=0 | | -.6b=-3 | | 6s(-142857)= | | 3[5-3(4-c)]-5=5[3(5c-4)+2]-26 | | 2(v+3)-3=15 | | (12x+9)+(2x+21)=360 | | 5a(3.4b)= | | 7(2x-1)=8x-25 | | (2x+3)(9x+6)=43+2(3x+1)(3+1) | | -2.7(4y)= | | a=215.5t+2500 | | x^2+2x-2=-4x+5 | | -1.75g-8.75=3g+7.5 | | 4+4b-(2b+3)-(5b+9)= | | z-5z+7z= | | 6(x-5)-4x=3(4x-5) | | [3x+4]+7=2 | | 2(h+-2)-2=10 | | 5x^2-50x-125=0 | | x+(10-45)=84-74 | | 8=2(k+2) | | -9.1x=63.7 | | 6+6x=-4(6-3x) |